OWNERSHIP STRUCTURE AND THE CORPORATE GOVERNANCE ROLE OF DIVIDENDS - Lukas Setia Atmaja (University of Merdeka Malang, 2008)
This paper reviewed the theoretical and empirical literature on the relationshipbetween ownership structure and dividends. Agency theory suggested that dividend was servedto reduce agency problems between owners (or large controlling shareholders) and managers(or minority shareholders) by reducing the amount of free cash flow and increasing monitoringby external parties. It also proposed that ownership concentration and composition mightmitigate or exacerbate agency problems. We might expect substitutability or complementaryrelationship existed between dividend and ownership concentration/composition. Empiricalevidence showed that the relationship between dividend and managerial or large shareholdingscould be negative (i.e., consistent with substitute argument), positive (i.e., consistent withcomplementary argument) or non-linear (i.e., consistent with entrenchment hypothesis). Inaddition, the literature suggested that family controlled firms might expropriate minorityshareholders by paying lower dividends or mitigate moral hazard conflicts by distributingmore cash. Empirical research on this issue, however, provided mixed findings.